2010
DOI: 10.1590/s1413-78522010000100002
|View full text |Cite
|
Sign up to set email alerts
|

Resultados do tratamento artroscópico das rupturas do manguito rotador

Abstract: OBJETIVO: Analisar os resultados do reparo artroscópico das rupturas do manguito rotador. MÉTODOS: Realizado estudo retrospectivo com avaliação dos resultados da técnica em 42 pacientes operados entre 2002 e 2006. O seguimento médio foi de 31 meses e a média de idade foi de 57 anos, sendo o lado dominante operado em 73,8% dos casos. Para avaliação foram usadas escalas de UCLA e Escala Visual Analógica da dor no pós-operatório. RESULTADOS: Os resultados foram satisfatórios em 85,7% (59,5% excelentes e 26,2% bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 12 publications
1
4
0
5
Order By: Relevance
“…Our results were similar to studies that showed improvement in pain and discomfort after rotator cuff repair, and that showed improvement in functional scores [3] and pain [31][32][33]. Another study that also evaluated two groups submitted to rotator cuff repair and used platelet rich plasma reported better pain reduction in the platelet rich group in comparison to the control group [28,34]. Movement amplitude was also associated with better improvement ratings in the stem cell group in comparison to the control group; the improvement, however, was only for the shoulder flexion movement.…”
Section: Discussionsupporting
confidence: 89%
“…Our results were similar to studies that showed improvement in pain and discomfort after rotator cuff repair, and that showed improvement in functional scores [3] and pain [31][32][33]. Another study that also evaluated two groups submitted to rotator cuff repair and used platelet rich plasma reported better pain reduction in the platelet rich group in comparison to the control group [28,34]. Movement amplitude was also associated with better improvement ratings in the stem cell group in comparison to the control group; the improvement, however, was only for the shoulder flexion movement.…”
Section: Discussionsupporting
confidence: 89%
“…This surgery provides satisfactory clinical results in more than 85% of patients. 4 , 5 , 6 , 7 , 8 However, the trend of increase in the number of rotator cuff repairs, from 31% to 238% in published historical series, 9 , 10 , 11 , 12 , 13 , 14 increases expenses of the healthcare system. 14 Thus, it is necessary to outline the Brazilian panorama to determine public policies that best serve the population.…”
Section: Introductionmentioning
confidence: 99%
“…The tendinous sutures on shoulder are efficient and, in a retrospective study, arthroscopic repair of injuries of the rotator cuff (RC) provides low surgical morbidity and enables diagnosis of associated joint injuries. The benefit of the procedure was corroborated especially by significant pain improvement, even in cases of larger injuries (27) . The knee movement pattern in the rest phase was different between children (mean age 9.7 years) and adults (mean age 25 years), which suggests that the maturation process of the normal gait may extend until the second decade of life (28) .…”
Section: Sports Orthopedics and Traumatologymentioning
confidence: 87%